Regulation of Raoultella terrigena comb.nov. phytase expression - Zamudio, Marcela; González, Aracely; Bastarrachea, Fernando (Canadian journal of microbiology, 2002)
Phytases catalyze the release of phosphate from phytate (myo-inositol hexakisphosphate) to inositol polyphosphates. Raoultella terrigena comb.nov. phytase activity is known to increase markedly after cells reach the stationary phase. In this study, phytase activity measurements made on single batch cultures indicated that specific enzyme activity was subject to catabolite repression. Cyclic AMP (cAMP) showed a positive effect in expression during exponential growth and a negative effect during stationary phase. RpoS exhibited the opposite effect during both growth phases; the induction to stationary phase decreased twofold in the rpoS::Tn10 mutant, but the effect of RpoS was not clearly determined. Two phy::MudI1734 mutants, MW49 and MW52, were isolated. These formed small colonies in comparison with the MW25 parent strain when plated on Luria-Bertani (LB) or LB supplemented with glucose. They did not grow in minimal media or under anaerobiosis, but did grow aerobically on LB and LB glucose at a lower rate than did MW25. The β-galactosidase activity level in these mutants increased three to four fold during stationary growth in LB glucose and during anaerobiosis. Addition of cAMP during the exponential growth of MW52 on LB glucose provoked a decrease in β-galactosidase activity during the stationary phase, confirming its negative effect on phytase expression during stationary growth.Key words: phytase activity, expression regulation, Raoultella terrigena.